ALTERNATIVE ASSESSMENT METHODS IN MODERN EDUCATION - Po’latova Sevinch; Xolnazarova Dinara; Jo’rabekova Robiya (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation (Annotatsiya) ; This article explores various alternative assessment methods used in modern education and evaluates their effectiveness in supporting student-centered learning. Through a review of current research and classroom practices, the study identifies how project-based assessment, portfolios, self-assessment, and peer assessment promote deeper learning and skill development. The findings show that alternative assessment encourages critical thinking, creativity, and learner autonomy while also providing a more holistic representation of student progress.